(untitled) (E Conference Zone, 2022)
This article gives general information about the main features of translation process from theoretical point of view, its types, forms and kinds. The problem of psychological peculiarities of the simultaneous interpretation will be analyzed by means of different approaches proposed by outstanding scholars in the field of the theory and practice of translation.